2009
DOI: 10.1302/0301-620x.91b2.21183
|View full text |Cite
|
Sign up to set email alerts
|

Early palsy of the sciatic nerve due to heterotopic ossification after surgery for fracture of the posterior wall of the acetabulum

Abstract: We describe a patient in whom an initially intact sciatic nerve became rapidly encased in heterotopic bone formed in the abductor compartment after reconstruction of the posterior wall of the acetabulum following fracture. Prompt excision and neural release followed by irradiation and administration of indometacin resulted in a full neurological recovery and no recurrence 27 months later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
(39 reference statements)
0
10
0
1
Order By: Relevance
“…Sciatic nerve injuries secondary to heterotopic ossification have been reported in the literature as case reports (6,8). The main characteristic of our case is heterotopic ossification was seen in the computed tomography taken at 6 weeks postoperatively, but symptoms occurred in the fourth month.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sciatic nerve injuries secondary to heterotopic ossification have been reported in the literature as case reports (6,8). The main characteristic of our case is heterotopic ossification was seen in the computed tomography taken at 6 weeks postoperatively, but symptoms occurred in the fourth month.…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic nerve injuries may also occur in patients treated surgically due to acetabular posterior wall / column fractures (4,5). In addition, the sciatic nerve can be trapped under pressure due to heterotopic ossification (HO), which develops at high rate after acetabulum fractures (6,7). In the sciatic nerve palsy developed by HO, there may be signs of weakness in the thigh region, in the tibialis anterior, extensor hallucis longus and peroneal muscle groups accompanying pain and paresthesia in the foot dorsum following the surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issack ha studiato retrospettivamente l'effetto del release del nervo sciatico associato a fratture acetabolari e chirurgia ricostruttiva acetabolare, concludendo che la neurolisi del nervo sciatico diminuisce con grande probabilità i sintomi sensitivi della neuropatia sciatica, mentre i deficit motori si risolvono con meno probabilità [25]. Poptodorov [26] e Manidakis [27] hanno documentato l'effetto positivo di una decompressione del nervo sciatico tramite neurolisi associata a rimozione delle ossificazioni.…”
Section: Gestione Delle Strutture Nervoseunclassified
“…Recently, interest in HO has increased as a result of its high prevalence in combat-related extremity injuries and amputations [9,10,14,15,17]. Studies have reported the prevalence of HO to be as high as 65% in combat-related amputations, and HO can result in pain, wound breakdown, difficulty with prosthesis wear, entrapment of neurovascular structures, and limited ROM [2,4,6,16,18,20,22,23,26,29,31,32,35]. Before operative excision, nonsurgical modalities such as pain control and serial prosthetic socket adjustments should be exhausted; however, up to 41% of affected patients who have undergone amputation will choose to have surgical excision to treat persistent symptoms and failed nonsurgical treatments [7,8,24,27,28].…”
Section: Introductionmentioning
confidence: 99%